Error Analysis in EFL Writing: Linguistics and Cultural Perspectives on Descriptive Paragraph Written by First-Year University Students - I Made Agus Adi Gunawan; Ni Wayan Krismayani (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2026)
This study investigates types, frequency and distribution of error in descriptive paragraph written by first-year university students. Error Analysis has been widely employed in English as a Foreign Language (EFL) research to investigate students' writing difficulties and interlanguage development. The analysis focused on three categories of error: grammatical, lexical, and mechanical errors. Moreover, this study incorporates linguistic and cultural perspectives to compare how those dimensions influence students’ errors. Descriptive qualitative approach is done, supported by quantitative frequency analysis is done by classifying errors made by students. The findings reveal that mechanical errors occur more frequently followed by grammatical and lexical. The most recurrent mechanical errors involve misplacement or omission of commas, full stop and capitalization. These errors indicate limited awareness of English writing conventions. This study suggests that EFL writing instruction should place greater emphasis on writing mechanics alongside with grammatical and lexical development to enhance students' writing accuracy.